Mechanics of Localized Slippage in Tactile Sensing And Application to Soft Sensing Systems - Ho, Anh-Van.; Hirai, Shinichi; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
Localized slippage occurs during any relative sliding of soft contacts, ranging from human fingertips to robotic fingertips. Although this phenomenon is dominant for a very short time prior to gross slippage, localized slippage is a crucial factor for any to-be-developed soft sensing system to respond to slippage before it occurs. The content of this book addresses all aspects of localized slippage, including modeling and simulating it, as well as applying it to the construction of novel sensors with slip tactile perception.
Introduction -- Two Dimensional Beam Bundle Model of a Frictional Sliding Soft Fingertip -- Three-Dimensional Beam Bundle Model of a Sliding Soft Fingertip -- Modeling of a Sliding Human Fingertip -- Tactile Sensing via Micro Force/Moment Sensor -- Slip Perception via Soft Robotic Skin Made of Electroconductive Yarn -- Slip Perception using a Tactile Array Sensor -- Concluding Remarks -- Appendix A: Continuous Modeling 2D Elastic Deformation -- Appendix B: Numerical Integration of Ordinary Differential Equations -- Appendix C: Integral over Triangle.
Keywords: Engineering; Artificial intelligence; Engineering; Computational Intelligence; Artificial Intelligence (incl. Robotics).